Socket preservation using acellular dermal matrix allograft in combination with xenograft for dental implant placement in Anterior Maxilla: a case report - Haslina Taib,; Khamiza Zainal Abidin,; Tara Bai Taiyeb Ali,; Norsiah Yunus, (Universiti Kebangsaan Malaysia, 2014)
The collapse of alveolar ridge following tooth extraction is a physiological process which may complicate subsequent implant placement and restoration especially in the aesthetic zone. This case report describes the use of an acellular dermal matrix graft (Alloderm®, Biohorizon, USA) in combination with bovine bone graft (Bio-Oss®, Geistlich, Switzerland) immediately after tooth extraction for soft and hard tissue augmentation prior to implant placement in the anterior maxilla. The eighth year follow-up demonstrated an acceptable aesthetic outcome indicating that this approach may be employed where tooth extraction is indicated and replacement with implant-supported prosthesis is anticipated particularly in the anterior aesthetic zone region.